Peranan Sektor Pariwisata Terhadap Pertumbuhan Ekonomi di Kabupaten Merauke - Hendricus Lembang; Yuliana Boby (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2020)
The purpose of this study is to determine the Role of the Tourism Sector on Economic Growth in Merauke Regency. To obtain research data, researchers interviewed 13 informants. This research uses a qualitative method with a descriptive approach, while the data analysis technique uses three stages: Data Reduction, Data Display, Verification (Conclusion Drawing). The results of this study indicate that the role of the tourism sector in Merauke Regency is not yet optimal so that cooperation between the local government, the Tourism Office, the private sector and the community has not been given much attention. This can be seen from the 8 variables: Tourism Objects, Accommodation, Access to Transportation, Food and Restaurant Services, Money Changers, Cultural Attractions, Souvenirs, and the last is Tourism Climate.